Protective effect of Phaleria macrocarpa (Scheff.) Boerl extract on the testicular damage of streptozotocin and nicotinamide-induced type 2 diabetic rats - Evy Sulistyoningrum, Danny Martha Pradipta, Sausan Fanana, Jamilah Aulia Haikhah, Malombassi Dharmawan Hadiwidjojo Putro (Journal of Applied Pharmaceutical Science, 2018)
There was an increase in the global prevalence of diabetes mellitus, especially type 2 DM, resulting in higher prevalence of diabetic complication. Persistent hyperglycemia in diabetes mellitus induces systemic oxidative stress in testis. Oxidative stress disrupts germinal cells and caused abnormalities in the male reproductive system. Phaleria macrocarpa (Scheff.) Boerl contains active substances which have antidiabetic properties and also reduced the severity of diabetic complication in recent studies. This research aimed to evaluate the protective effect of PM pericarp extract on the testicular oxidative marker and testicular histological changes of type 2 DM-induced by streptozotocin and nicotinamide. Twenty male albino (Sprague Dawley) rats were divided into four equal groups: normal control; diabetic; diabetic + vitamin E 100 mg/kg; diabetic + PM methanolic extract 250 mg/kg. Diabetes was induced by injection of streptozotocin 65 mg/kg and nicotinamide 230 mg/kb intraperitoneally. PM extract and vitamin E (as a comparison group) were administered to diabetic rats for six weeks and at the end of the study, subjects were sacrificed to obtain their testes for routine staining and malondialdehyde (MDA) analysis. Treatment with PM extracts and vitamin E significantly reduced testicular MDA level compared with an untreated diabetic group (p < 0.01). Treatment with PM extract significantly improved sperm count, spermatogenic score, seminiferous tubule epithelial thickness, Sertoli and Leydig cell’s number which is reduced in untreated diabetic groups. It was concluded that PM extracts improved testicular damage and testicular MDA level.
Keywords: Phaleria macrocarpa (Scheff.) Boerl., testicular MDA, testicular damage, type 2 diabetes mellitus.